Kontribusi Pendidikan Karakter di Pondok Pesantren Nurul Islam - Nurul Yaqin; M. Fahrurrozi (Universitas Islam Negeri (UIN) Mataram, 2022)
Hings that should not be eroded by the times are the cultivation of good character in educating students. One of the methods applied in recent years is the development of character education. The purpose of this study was to determine the impact of character education in Pondok Pesantren Nurul Islam using a qualitative approach with the type of case study. The subjects in this study were the parties involved in the management of the Nurul Islam Islamic Boarding School (boarding leaders, managers, foundations, teachers, students, alumni, and so on as data sources), Collecting data in the field using participatory observations (observations), interviews depth and documentation. Data analysis techniques with flow models and interactive models proposed by Miles and Huberman are data collection, data reduction, data presentation and conclusions or verification